2020
DOI: 10.1029/2020sw002440
|View full text |Cite
|
Sign up to set email alerts
|

Solar Flare Intensity Prediction With Machine Learning Models

Abstract: We develop a mixed long short-term memory (LSTM) regression model to predict the maximum solar flare intensity within a 24-hr time window 0-24, 6-30, 12-36, and 24-48 hr ahead of time using 6, 12, 24, and 48 hr of data (predictors) for each Helioseismic and Magnetic Imager (HMI) Active Region Patch (HARP). The model makes use of ( 1) the Space-Weather HMI Active Region Patch (SHARP) parameters as predictors and (2) the exact flare intensities instead of class labels recorded in the Geostationary Operational En… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 20 publications
0
30
0
Order By: Relevance
“…Second, we developed an innovative mixed LSTM regression model, which combines binary classification of flaring and LSTM regression for flare intensity, that was used to predict the flare onset jointly with the maximum solar flare intensity observed by the GOES satellites within a 24-hr time window (Jiao et al, 2020). The predicted intensity peaks are shown by light blue curves in Figure 26.…”
Section: Neural Network Predictions Of Solar Flaresmentioning
confidence: 99%
“…Second, we developed an innovative mixed LSTM regression model, which combines binary classification of flaring and LSTM regression for flare intensity, that was used to predict the flare onset jointly with the maximum solar flare intensity observed by the GOES satellites within a 24-hr time window (Jiao et al, 2020). The predicted intensity peaks are shown by light blue curves in Figure 26.…”
Section: Neural Network Predictions Of Solar Flaresmentioning
confidence: 99%
“…Zhenbang et al developed a mixed LSTM regression model to predict the maximum solar flare intensity within a 24-hr time window 0-24, 6-30, 12-36, and 24-48 hr ahead of time using 6, 12, 24, and 48 hr of data for each Helioseismic and Magnetic Imager (HMI) Active Region Patch (HARP) [27].…”
Section: B Solar Flaresmentioning
confidence: 99%
“…Recently, the application of supervised machine learning methods, especially deep neural networks (DNNs), to solar flare prediction has been a hot topic, and their successful application in research has been reported (Huang et al 2018;Nishizuka et al 2018;Park et al 2018;Chen et al 2019;Domijan et al 2019;Liu et al 2019;Zheng et al 2019;Bhattacharjee et al 2020;Jiao et al 2020;Li et al 2020;Panos & Kleint 2020;Yi et al 2020). However, there is insufficient discussion on how to develop the methods available to real-time operations in space weather forecasting offices, including the methods for validation and verification of the models.…”
Section: Introductionmentioning
confidence: 99%